The role of central bank transparency for guiding private sector forecasts - Michael Ehrmann; Sylvester Eijffinger; Marcel Fratzscher (European Central Bank (ECB), 2010)
There is a broad consensus in the literature that costs of information processing and acquisition may generate costly disagreements in expectations among economic agents, and that central banks may play a central role in reducing such dispersion in expectations. This paper analyses empirically whether enhanced central bank transparency lowers dispersion among professional forecasters of key economic variables, using a large set of proxies for central bank transparency in 12 advanced economies. It finds evidence for a significant and sizeable effect of central bank transparency on forecast dispersion, be it by means of announcing a quantified inflation objective, other forms of communication, or by publishing central banks' inflation and output forecasts. However, there also appear to be limits to central bank transparency, with decreasing marginal returns to enhancing (economic) transparency, and given our findings that disagreement among inflation expectations in the general public is not affected by the various central bank transparency measures analyzed in this paper.
Keywords: E37; E52; C53; 330; central bank communication; central banking; disagreement; forecasting; inflation targeting; monetary policy; survey expectations; transparency; Informationskosten; Wirtschaftsprognose; Zentralbank; Geldpolitik; Inflationssteuerung; Ankündigungseffekt; Industrieländer